Effect Of CaO, CuO AND V2O5 On Barium Zinc Tantalate (BZT) Dielectric Properties - Jaafar, Hidayani (2011)
BZT has high dielectric constant (εr) and low dielectric loss (tan δ). However, the formation of BZT using solid state method required high sintering temperature to produce excellent dielectric properties. Therefore, to overcome these problems, other elements were added in BZT and investigate the effect of reducing sintering temperature of BZT by doping with by CaO, CuO and V2O5 respectively. CaO was selected as a doping compound because the Ca substitution form a new structured and avoid deteriorated dielectric properties in high frequency range.